2018
DOI: 10.1155/2018/4143636
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Perfusion and Cerebral Autoregulation after Cardiac Arrest

Abstract: Out of hospital cardiac arrest is the leading cause of death in industrialized countries. Recovery of hemodynamics does not necessarily lead to recovery of cerebral perfusion. The neurological injury induced by a circulatory arrest mainly determines the prognosis of patients after cardiac arrest and rates of survival with a favourable neurological outcome are low. This review focuses on the temporal course of cerebral perfusion and changes in cerebral autoregulation after out of hospital cardiac arrest. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
51
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 45 publications
0
51
1
Order By: Relevance
“…21,23,31 Hyperperfusion in the subacute stage after cerebral ischemia is explained by loss of vascular autoregulation. 21,32 Early stage cerebral hyperperfusion is associated with ongoing brain injury and therefore subsequent brain changes are visible in conventional MRI sequences. [21][22][23]31,32 Hyperperfusion evidenced in this dog affected by CLN is consistent with findings reported in an experimental study, where hyperperfusion of compromised brain areas was detected 1 week after induced ischemic events in Beagle dogs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21,23,31 Hyperperfusion in the subacute stage after cerebral ischemia is explained by loss of vascular autoregulation. 21,32 Early stage cerebral hyperperfusion is associated with ongoing brain injury and therefore subsequent brain changes are visible in conventional MRI sequences. [21][22][23]31,32 Hyperperfusion evidenced in this dog affected by CLN is consistent with findings reported in an experimental study, where hyperperfusion of compromised brain areas was detected 1 week after induced ischemic events in Beagle dogs.…”
Section: Discussionmentioning
confidence: 99%
“…21,32 Early stage cerebral hyperperfusion is associated with ongoing brain injury and therefore subsequent brain changes are visible in conventional MRI sequences. [21][22][23]31,32 Hyperperfusion evidenced in this dog affected by CLN is consistent with findings reported in an experimental study, where hyperperfusion of compromised brain areas was detected 1 week after induced ischemic events in Beagle dogs. 33 Perfusion values in the apparently normal brain parenchyma in the left hemisphere of the dog that suffered the consequences of brain hypoxia were comparable to the control dog CBF values (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Patients in cardiac arrest lose haemodynamic autoregulation, commonly causing cerebral oedema (Brule et al,2018) to nullify this pathology (Malaguit et al, 2017). Consistently, as displayed in Table 1, ICP has been documented to decrease with elevating the patient, whether by a full body tilt or by elevating the head and thorax (Ryu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, only 10% of OHCA survivors who are discharged from hospital have neurological sequelae that make assistance with activities of daily living necessary 2 , while the prevalence of cognitive dysfunction is two to three times higher 3 . The cerebral blood flow (CBF) following return of spontaneous circulation (ROSC) after cardiac arrest typically involves a phase of initial hyperaemia (up to 20 minutes) followed by vasospasm and hypoperfusion (up to 12 hours) and then a gradual return to normal perfusion over 72 hours [4][5][6][7] . The phase of hypoperfusion in particular represents a plausible window of opportunity for interventions to support CBF and ameliorate hypoxic ischaemic encephalopathy.…”
Section: Introductionmentioning
confidence: 99%
“…The cerebral arteriolar resistance vessels are instrumental to maintain a homeostatic CBF by cerebrovascular autoregulation (CVAR) and are influenced by mean arterial pressure (MAP), carbon dioxide (P a CO 2 ) and oxygen (P a O 2 ) levels 8,9 . Several studies have reported an impaired CVAR following cardiac arrest 7,[10][11][12][13] . An impaired CVAR renders the CBF flow passively pressure dependent and places the brain at risk of hypoperfusion or hyperperfusion as MAP decreases or increases, further compounded by hypoxia/hyperoxia and/or hypocapnia/hypercapnia.…”
Section: Introductionmentioning
confidence: 99%